The role of augmented reality marketing in sustaining customer loyalty -An analytical study of the opinions of a sample of customers of some beauty centers in Misan - Lecturer. Hind Naeem Hoshi (Global Scientific Publishing, 2025)
The aim of the current research is to identify the extent of application of augmented reality marketing and its impact on the sustainability of customer loyalty to the services provided by the sample studied, and to find out whether this marketing tool is effective and valuable in the field of marketing, as the independent variable, augmented reality marketing, was studied with a group of dimensions represented by (quality of enhancement). , benefits of pleasure, ease of use, experience in augmented reality, nostalgia for the past, wonderful effect) As for the dependent variable, sustainability of customer loyalty, it was studied as a unidimensional variable. In addition, a sample of 219 customers was targeted, as well as a group of statistical programs such as the program SPSS and AMOS, and the research reached a set of conclusions, the most important of which was: There is interest by the researched sample in this marketing strategy based on technology and digital diversity, which aims to expand the customer’s vision and enhance his sustainability in obtaining the cosmetic service provided by the researched sample, in a way that brings him pleasure and satisfaction. As well as a set of recommendations, including: The researched sample seeks to keep pace with everything that is new and advanced in the world of marketing in order to strengthen its position among competitors and achieve a permanent and continuous mark with its customers.
Keywords: Augmented reality; marketing -Sustaining; customer loyalty